KAJIAN POTENSI LANSKAP JALUR KERETA REL LISTRIK (KRL) BOGOR -JAKARTA KOTA SEBAGAI KORIDOR PERGERAKAN BURUNG - Ramandini Puspita Sari; Syartinilia Wijaya; Aris Munandar (Jurnal Lanskap Indonesia, 2013)
ABSTRACTCorridors are narrow strips of land which differ from the matrix on either side. There are two types of corridors, namely linear corridor and stepping stone. One example of corridor is a landscape along the path of KRL Railway Bogor-Jakarta Kota. Corridor is important for bird movement. Nowadays there is habitat fragmentation along the corridor which is threatened their corridor function. Therefore it should be maintained for sustainable corridor. This study was conducted at corridor along the KRL Railway Bogor-Jakarta Kota which is divided into five segment. Three analyses were used in this study, i.e. corridor distribution analysis, vegetation analysis and bird abundance analysis. Stepping stone corridor has higher number of bird abundance than the linear corridor. Both of corridors have the potential to become a habitat of birds which is indicated by abundance species of birds. The highest abundance of a bird was found in corridor with diversity of plants (Shannon Wienner Index) in the medium level. Several recommendation have provided for managing the corridor such as managing and revitalizing the corridor, increasing vegetation diversity and increasing public awareness for bird habitat conservationKeywords : birds, GIS, habitat fragmentation, linear corridor, stepping stone